2017
DOI: 10.1038/s41598-017-05382-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Interleukin-12 activity in the presence of heparin

Abstract: Glycosaminoglycans (GAGs), especially heparin and heparan sulfate (HS), modulate the functions of numerous cytokines. The aims of this multidisciplinary research were to characterize heparin binding to interleukin-12 (IL-12) and determine the mechanism(s) by which heparin influences IL-12 bioactivity. Heparin and HS were found to bind human IL-12 (hIL-12) with low micromolar affinity and increase hIL-12 bioactivity by more than 6-fold. Conversely, other GAGs did not demonstrate significant binding, nor did the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 51 publications
5
28
2
Order By: Relevance
“…This apparent separation between the likely receptor binding sites and the heparin binding sites is consistent with our observations (data unpublished) that addition of sulfated GAGs including heparin and HS neither inhibits nor potentiates murine IL-12 bioactivity in the KY-1 cellular assay [33] . Subsequently, in studies of human IL-12 in human natural killer cell line NK-92MI and with human peripheral blood mononuclear cells, heparin was found to potentiate IL-12 activity [49] . Although this apparent species difference may arise from variations between the assay systems employed, it is also consistent with the difference we propose between the heparin binding sites of murine and human IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent separation between the likely receptor binding sites and the heparin binding sites is consistent with our observations (data unpublished) that addition of sulfated GAGs including heparin and HS neither inhibits nor potentiates murine IL-12 bioactivity in the KY-1 cellular assay [33] . Subsequently, in studies of human IL-12 in human natural killer cell line NK-92MI and with human peripheral blood mononuclear cells, heparin was found to potentiate IL-12 activity [49] . Although this apparent species difference may arise from variations between the assay systems employed, it is also consistent with the difference we propose between the heparin binding sites of murine and human IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…In support to this, in vivo inhibition of CXCL12/HS interaction using sulfated polysaccharide tilted the chemokine distribution from bone marrow toward the plasma, thereby causing the release of hematopoietic progenitor cells in the blood circulation (16). HS also mediates chemokine transcytosis across the endothelial cell wall (17,18), and protects chemokines/cytokines from enzymatic degradation and inactivation (19)(20)(21). Finally, HS may further modulate chemokine activity by inducing chemokine oligomerization [for review, see (11)], which has been shown to be functionally relevant in vivo (13).…”
Section: Hs In Inflammationmentioning
confidence: 96%
“…Soluble HS fragments released in inflammation may also regulate signaling of some cytokines by promoting their interaction with receptors on target cells. It has been demonstrated that addition of soluble HS to cells that lack detectable levels of this GAG on their surface augments IL‐5‐induced proliferation and IL‐12‐stimulated IFN‐γ production . The mechanism by which soluble HS promotes signaling of these cytokines has not been explored, and the relevance of these observations to inflammatory processes in vivo is not yet clear.…”
Section: Hs In the Microenvironment Regulates The Activities Of Immunmentioning
confidence: 99%